Building Teachers' Resilience: Practical Applications for Teacher Education of China - Wang, Yi (Frontiers in Psychology, 2021)
Teacher resilience has a crucial role to play in teaching and teacher education all around the world. However, few practical attempts have been made to systematically improve and (re)build this characteristic in teachers. Against this backdrop, this article draws on a universal model to offer practical implications of building resilience in the teacher education of China which is largely oriented toward pedagogical and economic concerns rather than the socio-emotional aspects of teaching. More particularly, it explains the history of China’s teacher education, the conceptualizations and significance of teacher resilience, and a systematic model to integrate resilience into teacher education. Finally, some practical implications and future directions are provided for avid scholars.